Commercialization as a recommended approach to hospital restructuring: Case study of Łańcut Medical Center - Wiktor Patena; Bartłomiej Kaszyk (e-Finanse: Financial Internet Quarterly, 2015)
Our society is on the brink of health care system reorganization and implementation of new medical technology. Hospitals have to be a core component of the medical revolution so they have to be prepared for the upcoming leap in their development. If Poland wants to be a pioneer in providing new medical solutions, the current ineffective system has to be changed. The necessary action should be taken to deal with the financial problems Polish hospitals have faced for over 20 years. The current structure of hospitals - SPZOZ, is old-fashioned and cannot adapt to a turbulent social and economic environment. The hospitals should be commercialized and restructured. Being capitalized companies will give incentives and new tools to deal with financial problems. The article presents an example of the commercialized hospital in ancut. We make the observations that commercialization increases: a hospital's profitability, its employment productivity, its capital investment spending and leverage. The case proves that the transformation of hospitals to capital companies proposed by the Ministry of Health may be an appropriate approach and it does work once a reasonable management board is in charge. However, the legal structure alteration should be treated as the first step in the overall restructuring process. The article highlights the problem of managers of Polish hospitals who do not only struggle with financial shortages, but barely know which business model they should follow after commercialization to successfully run the restructuring process. Having examined the LMC the authors are crafting a prelude to the overall research on already commercialized hospitals to find an appropriate business model.
Keywords: C53; G38; H51; I18; 330; health care system; hospital restructuring; commercialization; hospital operational performance